The choice of therapeutic tactics in a patient with diagnosed breast cancer and lung neoplasm - N. Yu. Germanovich; M. Yu. Pikunov; T. A. Shchegolkova; I. M. Mishchenko (Акушерство, гинекология и репродукция, 2024)
Breast cancer (BC) has long held a leading position in oncology disease pattern among global female population. Statistics data show that BC metastasis to lung tissue accounts for 21–32 % of all distant metastasis cases. Pulmonary metastases usually occur within 5 years after initial BC diagnosis, more often affecting peripheral lung parts, which explains the difficulty for their differential diagnosis. In addition, they profoundly impact on disease course and patient survival rate, so that each case of combined pathology such as BC and lung solid neoplasm is of interest in terms of clinicopathologic features as well as the diagnostic approach, with subsequent choice of surgical treatment tactics. Obviously, a therapeutic strategy in such cases is based on knowing primary tumor morphological structure and verifying metastatic process. However, in case of small sized pulmonary focus, it is difficult to identify a modality of ongoing process. Currently, no therapeutic and diagnostic tactics in such cases have been developed in detail. Assessing the clinical case of a combined ВС and a single small-sized focal lung mass, we propose an effective diagnostics and treatment scheme.